2018
DOI: 10.1128/mbio.00008-18
|View full text |Cite
|
Sign up to set email alerts
|

Mouse and Human Monoclonal Antibodies Protect against Infection by Multiple Genotypes of Japanese Encephalitis Virus

Abstract: Japanese encephalitis virus (JEV) remains a leading cause of viral encephalitis worldwide. Although JEV-specific antibodies have been described, an assessment of their ability to neutralize multiple genotypes of JEV has been limited. Here, we describe the development of a panel of mouse and human neutralizing monoclonal antibodies (MAbs) that inhibit infection in cell culture of four different JEV genotypes tested. Mechanism-of-action studies showed that many of these MAbs inhibited infection at a postattachme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 63 publications
3
50
0
Order By: Relevance
“…Previous studies have shown that antibody-mediated immune responses against flaviviruses are protective (Nybakken et al, 2005;Sapparapu et al, 2016;Shrestha et al, 2010;Fernandez et al, 2018). The identification of the mechanisms of neutralization and key epitopes of potently neutralizing antibodies has implications for antibody-based therapies and vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that antibody-mediated immune responses against flaviviruses are protective (Nybakken et al, 2005;Sapparapu et al, 2016;Shrestha et al, 2010;Fernandez et al, 2018). The identification of the mechanisms of neutralization and key epitopes of potently neutralizing antibodies has implications for antibody-based therapies and vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Passive transfer of minute quantities of immune serum from WNV‐convalescent mice into B‐cell‐deficient animals confers protection to homologous virus infection . Analysis of mouse monoclonal antibodies has revealed that the most potent neutralizing epitopes are located on the lateral ridge epitope of DIII (DIII‐lr) . Interestingly, these DIII‐lr‐specific antibodies are immunodominant in mice, whereas in humans, these specificities clearly exist but are overwhelmed by DII‐fl‐reactive cells and antibodies .…”
Section: Flavivirus Pathogenesis Epidemiology and Immunitymentioning
confidence: 99%
“…2 Analysis of mouse monoclonal antibodies has revealed that the most potent neutralizing epitopes are located on the lateral ridge epitope of DIII (DIIIlr). 45,[60][61][62][63] Interestingly, these DIII-lr-specific antibodies are immunodominant in mice, whereas in humans, these specificities clearly exist but are overwhelmed by DII-flreactive cells and antibodies. 38,45,46,64 The DIII-lr epitope is only weakly conserved across flavivirus species, so longlived plasma cell DIII-lr responses provide type-specific immunity with minimal ability to promote ADE.…”
Section: Non-protective and Protective Antibodies In Response To Flavmentioning
confidence: 99%
“…Due to similarities within viral families, this research could have far-reaching consequences for rendering mosquitoes resistant to other arboviruses like ZIKV and CHIKV by using similar genetic engineering strategies to develop scFv-based transgenes. Multiple potent antibodies that effectively neutralize these various mosquito-borne viruses have also been identified in the last decade [57][58][59][60][61] . Although not all of these will confer robust viral resistance when expressed in vivo in mosquitoes, the availability of diverse, well-characterized antibodies of this sort, largely as a result of antibody therapeutic development efforts 58 , should allow for the identification of those that function within the desired context.…”
Section: Discussionmentioning
confidence: 99%